2022
DOI: 10.1038/s41467-022-31156-z
|View full text |Cite
|
Sign up to set email alerts
|

Dynamic interaction of BRCA2 with telomeric G-quadruplexes underlies telomere replication homeostasis

Abstract: BRCA2-deficient cells precipitate telomere shortening upon collapse of stalled replication forks. Here, we report that the dynamic interaction between BRCA2 and telomeric G-quadruplex (G4), the non-canonical four-stranded secondary structure, underlies telomere replication homeostasis. We find that the OB-folds of BRCA2 binds to telomeric G4, which can be an obstacle during replication. We further demonstrate that BRCA2 associates with G-triplex (G3)-derived intermediates, which are likely to form during direc… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
41
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 13 publications
(43 citation statements)
references
References 78 publications
(102 reference statements)
2
41
0
Order By: Relevance
“…Guanine quadruplexes (GQs) are a common non-canonical form of nucleic acids. They are formed by sequences rich in guanine (G), which are widespreadhundreds of thousands of known and putative sites have been identified in the human genome. , Notably, GQs are abundant in gene regulatory parts and in the telomeric region, where they play roles in maintaining cell function and genome integrity. Mutations leading to over- or under-formation of G4s often lead to diseases, such as cancer or neuropathologies. …”
Section: Introductionmentioning
confidence: 99%
“…Guanine quadruplexes (GQs) are a common non-canonical form of nucleic acids. They are formed by sequences rich in guanine (G), which are widespreadhundreds of thousands of known and putative sites have been identified in the human genome. , Notably, GQs are abundant in gene regulatory parts and in the telomeric region, where they play roles in maintaining cell function and genome integrity. Mutations leading to over- or under-formation of G4s often lead to diseases, such as cancer or neuropathologies. …”
Section: Introductionmentioning
confidence: 99%
“…Consistent with these findings, we showed that BRCA2 is required for the formation of C-circles, an important ALT biomarker, in ALT+ cells that experience severe replication stress at their telomeres ( Pan et al, 2019 ). Most intriguingly, Lee and colleagues demonstrated recently that BRCA2 directly binds the telomeric G4s in vitro , suggesting that it may be involved in disrupting the G4 accumulation, thereby preventing replication fork stalling at telomeres ( Lee et al, 2022 ).…”
Section: Molecular Mechanism Behind the Clinical Efficacy Of Parp Inh...mentioning
confidence: 99%
“…We recently reported that BRCA2 recognizes dynamically interconverting telomere G-quadruplex (G4), a G-rich four-stranded nucleic acid structure. Specifically, we demonstrated that BRCA2 directly binds to G-triplex (G3) intermediates during dynamic interconversion between parallel and non-parallel telomeric G4s ( 9 ). The binding of BRCA2 to G3 protects telomeric G4, which would otherwise be susceptible to attack by nuclease MRE11.…”
Section: Introductionmentioning
confidence: 99%
“…The binding of BRCA2 to G3 protects telomeric G4, which would otherwise be susceptible to attack by nuclease MRE11. At the same time, BRCA2 binding to G3 enables RAD51 loading to single-stranded regions in G3, facilitating the remodeling of the stalled replication fork and restarting telomere replication ( 9 ).…”
Section: Introductionmentioning
confidence: 99%